The Forty-Sixth Euro Congress on Drug Synthesis and Analysis: Snapshot † - Pavel Mucaji; Atanas G. Atanasov; Andrzej Bak; Violetta Kozik; Karolina Sieron; Mark Olsen; Weidong Pan; Yazhou Liu; Shengchao Hu; Junjie Lan; Norbert Haider; Robert Musiol; et al. (Molecules, 2017)
The 46th EuroCongress on Drug Synthesis and Analysis (ECDSA-2017) was arranged within the celebration of the 65th Anniversary of the Faculty of Pharmacy at Comenius University in Bratislava, Slovakia from 5–8 September 2017 to get together specialists in medicinal chemistry, organic synthesis, pharmaceutical analysis, screening of bioactive compounds, pharmacology and drug formulations; promote the exchange of scientific results, methods and ideas; and encourage cooperation between researchers from all over the world. The topic of the conference, “Drug Synthesis and Analysis,” meant that the symposium welcomed all pharmacists and/or researchers (chemists, analysts, biologists) and students interested in scientific work dealing with investigations of biologically active compounds as potential drugs. The authors of this manuscript were plenary speakers and other participants of the symposium and members of their research teams. The following summary highlights the major points/topics of the meeting.